2012
DOI: 10.1111/j.1532-5415.2012.03899.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Delirium in Older Adults with Recent Hip Fracture Through Multidisciplinary Geriatric Consultation

Abstract: Delirium episodes and cognitive decline during hospitalization were found to be common in older adults with hip fracture, as expected, but an IGCT intervention reduced the incidence of these adverse outcomes. In participants who developed delirium, a geriatric consultation had no effect on severity or duration of the delirium episode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
165
4
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(176 citation statements)
references
References 29 publications
4
165
4
3
Order By: Relevance
“…In studies regarding the non-pharmacologic, multicomponent, and multi-disciplinary counseling protocol for delirium prevention, the intervention was found to be effective in reducing the incidence of delirium (Deschodt et al, 2012;Inouye et al, 1999;Martinez et al, 2012). A .71 a reduced delirium incidence, length of hospitalization, and medical costs were observed in a study regarding the application of a specialized delirium prevention program, which was developed as part of the Hospital Elder Life Program for hospitalized elderly patients (Rubin et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…In studies regarding the non-pharmacologic, multicomponent, and multi-disciplinary counseling protocol for delirium prevention, the intervention was found to be effective in reducing the incidence of delirium (Deschodt et al, 2012;Inouye et al, 1999;Martinez et al, 2012). A .71 a reduced delirium incidence, length of hospitalization, and medical costs were observed in a study regarding the application of a specialized delirium prevention program, which was developed as part of the Hospital Elder Life Program for hospitalized elderly patients (Rubin et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Friedman et al retrospectively reviewed 193 patients that received an orthogeriatric joint model of care and compared them with 121 patients who received a reactive consultation model. They found that there was a statistically significant reduction in post-operative infection, venous thromboembolism and cardiac complications within the joint care group [47].The 2012 prospective controlled trial by Deschodt et al compared a model of care that involved regular peri-operative orthogeriatric assessment with a usual model of care and found a statistically significant higher number of No improvement in functional outcome in intervention group *Significant difference between control and intervention episodes of delirium in the latter group, along with more cognitive decline at the time of hospital discharge [49]. Randomised controlled trial by Marcantonio et al in 2001 compared the effect of regular peri-operative geriatric review of patients with hip fracture with a usual model of care, and the authors reported that their proactive geriatric consultation intervention reduced delirium by over one third [74].…”
Section: Effect Of Orthogeriatric Management On Inpatient Morbiditymentioning
confidence: 95%
“…Compared to a usual model of care: -Reduced inpatient mortality rates [46] Compared to a usual model of care: -Reduced length of stay [48] Compared to a usual model of care: -Reduced incidence of delirium in patients [49] -Reduced time to surgery [48] -Improved post-operative patient self-care, mobility and depressive symptoms [50] 3. Post-operative geriatric rehabilitation unit…”
Section: Why Are Fragility Fractures Important?mentioning
confidence: 99%
“…To prevent and manage the occurrence of possible delirium (avoidable with a 30 % risk reduction when using a specialized geriatric intervention [32,37,38]), we used the recommendations proposed by Inouye et al [31,32] every day of hospitalization. Delirium is common after hip fracture surgery (occurring in 35% to 65% of patients) [37], frequently associated with preexisting cognitive impairment and it is predictive of functional decline, institutionalization, and mortality [33,37]: each day of delirium increased the risk of death within 6 months by 17% [34].…”
Section: Discussionmentioning
confidence: 99%